State asset utilization strategy through strategic asset leasing services: a case study of the Makassar office of information and communication technology management and state property - Muhammad Ridwan; Abdul Razak Munir; Wahda Wahda (Program Pascasarjana Universitas Negeri Makassar, 2023)
Optimizing the utilization of state assets through strategic asset leasing services is important in the context of effective public resource management. However, to achieve this goal, a systematic and integrated approach is required. Therefore, this study aims to combine the TOWS (threats, opportunities, weaknesses, strengths) method with SWOT (strengths, weaknesses, opportunities, threats) analysis to develop an optimal strategy for state asset utilization. This study aims to analyze internal and external factors affecting the utilization of state assets and identify suitable strategies using the TOWS approach. This study used a qualitative approach with SWOT analysis and TOWS matrix. Data were collected through a literature review and interviews with experts in the field of state asset management. Internal and external factors were analyzed to identify relevant strengths, weaknesses, opportunities, and threats in the context of state asset utilization. Based on SWOT analysis, several internal strengths and weaknesses of solar power development companies in South Sulawesi were identified. In addition, external opportunities and threats affecting the company were also identified. Then, using the TOWS matrix, suitable strategies were developed to optimize the utilization of state assets through strategic asset leasing services in the region. Combining the TOWS method with SWOT analysis provides a comprehensive approach in the development of state asset utilization strategies. This research produced a strategy that can be used as a guide in optimizing the utilization of state assets through strategic asset leasing services in South Sulawesi. This strategy considers internal strengths, weaknesses, opportunities, and external threats, so as to increase effectiveness and efficiency in the management of state assets.